Study case Remote Access for PCI DSS Compliance at Company in Jakarta - Sihotang, Rony Andry Anthony (Swiss German University, 2016)
The growth of electronic transactions in Indonesia has grown tremendously since the start of the government program of the Non-Cash National Movement (GNNT) by Bank Indonesia since 2014. It is expected that the use of cash will be replaced by electronic transactions (cashless) using ATM cards, debit cards, credit cards, electronic cards. Electronic transactions must be reliable and secure, this is what drives 5 international payment networks such as American Express, Discover, JCB, Mastercard and Visa create a data security standard to secure cardholder data PCI DSS (Payment Card Industry Data Security Standard). PCI DSS has always evolved to always keep cardholder data secure for transaction and now PCI DSS has released PCI DSS version 3.2 in April 2016. Employees need to connect to internal private networks or corporation’s network over the Internet from home or public areas such as hotels, airports, cafe mall etc. Security becomes a major consideration when access to internal networks or corporation’s network from insecure network. In this case study, one company with head office located in Jakarta, Indonesia with team development located in Seoul, South Korea. Also see the connection between convenience and security when implementing remote access in accordance with PCI DSS requirements.